Benefits and Difficulties of Gender Diversity on Software Development Teams: A Qualitative Study - Kohl, Karina; Prikladnicki , Rafael (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
There is a known and established gender imbalance in software engineering structures. The discussions about gender diversity in Software Engineering are on the table; however, which are the benefits and the difficulties people in software development teams see in gender diversity? For this work, we conducted a survey to qualitatively understand the perceived benefits and difficulties of gender diversity in software development teams. We found out that gender-diverse workplaces are prone to have better ideas sharing, better decision making, creativity, and innovation. Respondents mentioned that some companies worked to improve the hiring process to be more gender-inclusive. Women’s support and inspiration were shared, and some men reported being touched by the subject and diligently are deconstructing their prejudice and misconceptions about women in technology. There are also difficulties. It is common to see only one woman in teams or just a few. More than that, no other gender than men and women, so the white, cisgender man is the pattern most of the time. The same pattern repeats itself in leadership positions leading to male protectionism and privileges. Additionally, other dimensions of diversity pervaded the answers, like intersectionality, race/ethnicity, ageism, and a less explored point: social vulnerability.